Internalisasi Moderasi Beragama Melalui Tradisi Munjungan Di Dusun Sawur Desa Bulusari: Internalisas - Abdul Aziz, Muhammad; Masruroh, Sayidah Afyatul (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
Indonesia is known as a multicultural country that is rich with various tribes, religions and tastes. However, considering the abundant cultural, cultural and religious diversity throughout Indonesia, the Indonesian people have an urgent responsibility to strengthen the values ​​of tolerance and harmony between people. .Internalization of Religious Moderation Through the Munjungan Tradition. The first stage carried out was to determine the theme, namely the internalization of religious moderation through the munjungan tradition in the sawur village of Bulusari, with research objectives (1) the process of internalization of religious moderation, (1) supporting and inhibiting factors in the Munjungan tradition in Suwur Hamlet, Bulusari Village, District. Tarokan, Kab. Kediri. So this research uses a descriptive qualitative approach using social interaction theory to study it in depth. The research results show that the munjungan tradition has an important role in the process of internalizing various modes of moderation, namely respecting differences in beliefs, respecting religious plurality, attitudes of tolerance, building harmonious relationships and reducing conflict.